2021
DOI: 10.1021/acs.jpcb.1c06759
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Structure of a Water-in-Salt Electrolyte with a Remarkably Asymmetric Anion

Abstract: Water-in-salt systems, i.e., super-concentrated aqueous electrolytes, such as lithium bis(trifluoromethanesulfonyl)imide (21 mol/kg water ), have been recently discovered to exhibit unexpectedly large electrochemical windows and high lithium transference numbers, thus paving the way to safe and sustainable charge storage devices. The peculiar transport features in these electrolytes are influenced by their intrinsically nanoseparated morphology, stemming from the anion hydrophobic nature and manifesting as nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…The prepeak in the SWAXS patterns of liquids made of small molecules (i.e., molecules with a radius of gyration smaller than 1 nm) is not common, with some remarkable exceptions when amphiphilic molecules are concerned. [39][40][41][42][43][44][45] In those cases, the peak always originates from the formation of a distorted L 3 liquid phase, which is often referred as "sponge-like" [46] and which is basically a bicontinuous structure. The formation of this phase is driven by the amphiphilic nature of one (or more) species, which induce a self-segregation by preferentially orienting toward each other compatible molecules or portions of molecules, that is, polar with polar and apolar with apolar.…”
Section: Pre-peak and The Acetate Anion Dualismmentioning
confidence: 99%
“…The prepeak in the SWAXS patterns of liquids made of small molecules (i.e., molecules with a radius of gyration smaller than 1 nm) is not common, with some remarkable exceptions when amphiphilic molecules are concerned. [39][40][41][42][43][44][45] In those cases, the peak always originates from the formation of a distorted L 3 liquid phase, which is often referred as "sponge-like" [46] and which is basically a bicontinuous structure. The formation of this phase is driven by the amphiphilic nature of one (or more) species, which induce a self-segregation by preferentially orienting toward each other compatible molecules or portions of molecules, that is, polar with polar and apolar with apolar.…”
Section: Pre-peak and The Acetate Anion Dualismmentioning
confidence: 99%
“…Concentrated, correlated electrolytes could provide intriguing opportunities for leveraging both co-ions and counterions to modulate interface properties and microphase separation. For example, studies of water-in-salt electrolytes, where water is dissolved into salt to form a single-phase liquid that is predominantly salt, has revealed that the emergence of microphase separation in bulk electrolytes is primarily governed by the properties of anions. Hence, we envision that these effects will become more pronounced at electrochemical interfaces and provide promising avenues for controlling microphase separation phenomena in electrocatalytic processes.…”
Section: Intersection Of Electric Double Layer Properties and Electro...mentioning
confidence: 99%
“…In contrast, classical force fields allow MD simulations to be run for sufficiently large system sizes and long simulation times, but they suffer from a limited accuracy as far as the chemical interactions are concerned. So far, good efforts have been made to model WiS solutions using classical MD simulations for LiB electrolytes. However, there are only a few studies on NaB electrolytes.…”
Section: Introductionmentioning
confidence: 99%